An intensive model of care for hepatitis C virus screening and treatment with direct‐acting antivirals in people who inject drugs in Nairobi, Kenya: a model‐based cost‐effectiveness analysis. (28th July 2021) - Mafirakureva, Nyashadzaishe; Stone, Jack; Fraser, Hannah; Nzomukunda, Yvonne; Maina, Aron; Thiong'o, Angela W.; Kizito, Kibango Walter; Mucara, Esther W. K.; González Diaz, C. Inés; Musyoki, Helgar; Mundia, Bernard; Cherutich, Peter; et al.
Abstract: Background and aims: Hepatitis C virus (HCV) treatment is essential for eliminating HCV in people who inject drugs (PWID), but has limited coverage in resource‐limited settings. We measured the cost‐effectiveness of a pilot HCV screening and treatment intervention using directly observed therapy among PWID attending harm reduction services in Nairobi, Kenya. Design: We utilized an existing model of HIV and HCV transmission among current and former PWID in Nairobi to estimate the cost‐effectiveness of screening and treatment for HCV, including prevention benefits versus no screening and treatment. The cure rate of treatment and costs for screening and treatment were estimated from intervention data, while other model parameters were derived from literature. Cost‐effectiveness was evaluated over a life‐time horizon from the health‐care provider's perspective. One‐way and probabilistic sensitivity analyses were performed. Setting: Nairobi, Kenya. Population: PWID. Measurements: Treatment costs, incremental cost‐effectiveness ratio (cost per disability‐adjusted life year averted). Findings: The cost per disability‐adjusted life‐year averted for the intervention was 975, with 92.1% of the probabilistic sensitivity analyses simulations falling below the per capita gross domestic product for Kenya (1509; commonly used as a suitable threshold for determining whether an intervention is cost‐effective). However, the intervention was not cost‐effective at the opportunity cost‐based cost‐effectiveness threshold of 647 per disability‐adjusted life‐year averted. Sensitivity analyses showed that the intervention could provide more value for money by including modelled estimates for HCV disease care costs, assuming lower drug prices (75 instead of 728 per course) and excluding directly‐observed therapy costs. Conclusions: The current strategy of screening and treatment for hepatitis C virus (HCV) among people who inject drugs in Nairobi is likely to be highly cost‐effective with currently available cheaper drug prices, if directly‐observed therapy is not used and HCV disease care costs are accounted for.